Do ISO-Based Management Systems and Board Gender Diversity Enhance ESG Performance? Evidence from ASEAN Banks - Duwi Agustina; Rindu Rika Gamayuni; Agrianti Komalasari (Universitas Bangka Belitung, 2026)
The increasing pressure for sustainable business practices has encouraged banking firms in the ASEAN region to strengthen their environmental, social, and governance (ESG) performance. This study aims to examine the effect of ISO-based management systems (MS) and board gender diversity (BGD) on the ESG performance of ASEAN banks during the 2018–2023 period. Using a quantitative approach with panel data analysis, this study employed balanced panel observations from banking companies listed in five ASEAN countries. The estimation was conducted using the panel estimated generalized least squares (EGLS) method with the random effect model selected through several model specification tests. The findings reveal that ISO-based management systems have a positive and significant effect on ESG performance, indicating that the adoption of international management standards contributes to improving sustainability performance in the banking sector. In contrast, board gender diversity does not show a significant effect on ESG performance, which may be due to the relatively low proportion of female directors that has not yet reached the critical mass required to influence strategic decision-making effectively. The study concludes that ISO certification serves as an effective governance mechanism in promoting sustainability practices within ASEAN banking firms.